Persistent dynamics in the S=1/2 quasi-one-dimensional chain compound Rb4Cu(MoO4)(3) probed with muon-spin relaxation - Lancaster, T; Baker, P; Pratt, F; Blundell, S; Hayes, W; Prabhakaran, D (2012)
We report the results of muon-spin relaxation measurements on the low-dimensional antiferromagnet Rb 4Cu(MoO 4) 3. No long-range magnetic order is observed down to 50 mK implying a ratio T N/J<0.005 (where J is the principal exchange strength along the spin chains) and an effective ratio of interchain to intrachain exchange of |J ⊥/J|<2×10 -3, making the material an excellent realization of a one-dimensional quantum Heisenberg antiferromagnet. We probe the persistent spin excitations at low temperatures and find that ballistic spin transport dominates the excitations detected below 0.3 K. © 2012 American Physical Society.